2019
DOI: 10.3390/molecules24244505
|View full text |Cite
|
Sign up to set email alerts
|

Novel Homo-Bivalent and Polyvalent Compounds Based on Ligustrazine and Heterocyclic Ring as Anticancer Agents

Abstract: Bivalent and polyvalent inhibitors can be used as antitumor agents. In this experiment, eight ligustrazine dimers and seven ligustrazine tetramers linked by alkane diamine with different lengths of carbon chain lengths were synthesized. After screening their antiproliferation activities against five cancer cell lines, most ligustrazine derivatives showed better cytotoxicity than the ligustrazine monomer. In particular, ligustrazine dimer 8e linked with decane-1,10-diamine exhibited the highest cytotoxicity in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…TMP has the effects of inhibiting platelet aggregation, reducing blood viscosity, increasing coronary flow, scavenging free radicals, protecting cerebral vessels, and expanding renal vessels ( Zou et al, 2018 ). The pyrazine ring on the TMP molecule is the key group for its pharmacological effect, but the methyl group in its side chain is easily excreted by oxidative metabolism, which leads to the short half-life of TMP and weakens its pharmacological effect ( Wang et al, 2019 ). Pharmacokinetic studies have shown that after oral or intravenous injection, TMP is mainly distributed in tissues such as liver, brain, kidney, and small intestine, and is eventually excreted from urine through the kidney ( Lou et al, 1986 ; Pan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…TMP has the effects of inhibiting platelet aggregation, reducing blood viscosity, increasing coronary flow, scavenging free radicals, protecting cerebral vessels, and expanding renal vessels ( Zou et al, 2018 ). The pyrazine ring on the TMP molecule is the key group for its pharmacological effect, but the methyl group in its side chain is easily excreted by oxidative metabolism, which leads to the short half-life of TMP and weakens its pharmacological effect ( Wang et al, 2019 ). Pharmacokinetic studies have shown that after oral or intravenous injection, TMP is mainly distributed in tissues such as liver, brain, kidney, and small intestine, and is eventually excreted from urine through the kidney ( Lou et al, 1986 ; Pan et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…3,5,6‐Trimethylpyrazine‐2‐carboxylic acid and 2‐(bromomethyl)‐3,5,6‐trimethylpyrazine were prepared from tetramethylpyrazine (Ligustrazine). Details can be found in the reported method (Chen et al., 2015; Wang et al., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…[99][100][101] Numerous series of derivatives have been synthesized on the basis of ligustrazine including dimeric ones. 100,102,103 The patent 94 describes in detail the synthesis of bivalent compounds based on ligustrazine and securinine (Scheme 15) with the preliminary production of 2,5-bis(bromomethyl)-3,6dimethylpyrazine and aminosecurinine followed by their combination into a bivalent derivative. Thus, the use of a bivalent strategy for the synthesis of securinine derivatives is one of the promising trends for the production of active compounds.…”
Section: Bivalent Securinine Analoguesmentioning
confidence: 99%